Advancing knowledge, maps and tools to address obesity and related socio-economic disparities in Europe: the OBCT project - Thao Minh Lam; Julie Aarestrup; Erica L. T. van den Akker; Jennifer L. Baker; Anna Banik; Bram J. Berntzen; Lucrezia Bertoni; Joline W. j. Beulens; Kirsten Bjørnsbo; Sheree Bryant; Luis Cereijo; Priyanka Choudhary; et al. (Global Health Action)
The steady rise in overweight and obesity in Europe disproportionately affects people and communities with a lower socio-economic position (SEP). Many obesity prevention approaches exist, but these have had limited reach and unsatisfactory effects thus far, especially in low-SEP populations. In this context, there is a need for implementation of effective individual-level and population-based preventive strategies that also tackle health inequalities. Effective strategies require consideration of the complex and cross-domain obesity risk factors across the life course. Feasible and acceptable strategies require multisectoral collaborations and innovative approaches, including a whole-of community and systems perspective. With the Horizon Europe-funded OBCT project, we aim to quantify the relative contribution of biological, socio-cultural and built environment factors to obesity and the interactions of these risks within and across various life course stages; and translate the resulting knowledge into practical, equitable, and effective tools for action. These tools will include: a comprehensive obesity risk screener; a map of the obesogenicity of neighbourhood environments as well as trends in obesity prevalence of each European country; recommendations for lifestyle behaviours (diet, physical activity, sedentary behaviours) to prevent obesity during key life transition stages; a decision support dashboard for policy makers; and co-developed toolboxes to support implementation of policy recommendations in low-SEP communities. OBCT’s outputs will highlight the areas and domains in which obesity should be targeted and will empower the research community, policymakers, health professionals and residents in Europe to adapt and implement strategies to effectively reduce obesity risk, particularly in low-SEP communities.